Impaired neural stem cell expansion and hypersensitivity to epileptic seizures in mice lacking the EGFR in the brain. (4th August 2018) - Robson, Jonathan P.; Wagner, Bettina; Glitzner, Elisabeth; Heppner, Frank L.; Steinkellner, Thomas; Khan, Deeba; Petritsch, Claudia; Pollak, Daniela D.; Sitte, Harald H.; Sibilia, Maria
Abstract : Mice lacking the epidermal growth factor receptor (EGFR) develop an early postnatal degeneration of the frontal cortex and olfactory bulbs and show increased cortical astrocyte apoptosis. The poor health and early lethality of EGFR −/− mice prevented the analysis of mechanisms responsible for the neurodegeneration and function of the EGFR in the adult brain. Here, we show that postnatal EGFR‐deficient neural stem cells are impaired in their self‐renewal potential and lack clonal expansion capacity in vitro . Mice lacking the EGFR in the brain (EGFR Δbrain ) show low penetrance of cortical degeneration compared to EGFR −/− mice despite genetic recombination of the conditional allele. Adult EGFR Δ mice establish a proper blood–brain barrier and perform reactive astrogliosis in response to mechanical and infectious brain injury, but are more sensitive to Kainic acid‐induced epileptic seizures. EGFR‐deficient cortical astrocytes, but not midbrain astrocytes, have reduced expression of glutamate transporters Glt1 and Glast, and show reduced glutamate uptake in vitro, illustrating an excitotoxic mechanism to explain the hypersensitivity to Kainic acid and region‐specific neurodegeneration observed in EGFR‐deficient brains. Abstract : Epidermal growth factor receptor (EGFR) is important for proper brain development but the poor health and early lethality of EGFR –/– mice prevents the analysis of the mechanisms of EGFR in the adult brain. Maria Sibilia and colleagues have generated two conditional EGFR‐deficient mouse models. Using these models they show that deletion of EGFR in the developing brain results in reduced clonal expansion, reduced neuronal differentiation, and reduced glutamate transporter expression, leading to impaired neural development.